Using choice experiments to assess environmental impacts of dams in Portugal - Botelho, Anabela (2015)
Despite their well-known benefits in electricity production, dams are also responsible for some adverse environmental impacts affecting particularly the wellbeing of residents of the local communities. These environmental damages have not been included in the cost-benefit analysis of hydropower developments mainly because of the difficulty to determine their value. The prime objective of this paper is to measure the economic values of several environmental impacts due to the dams’ activity in Portugal, using a discrete choice experiments approach. With the results of this research paper, we expect to contribute to a more efficient and thorough cost-benefit analysis within the complex process of deciding the optimal location of future dams to be built not only in Portugal, but elsewhere. The addition of this stage to the decision-making process allows the integration of economic, social and environmental dimensions, promoting a richer and more informed decision process